Problemy wolności wiary religijnej, ukrytości Boga i dowodów istnienia Boga na przykładzie koncepcji Johna Hicka i jej krytyki - Strzyżyński, Przemysław (Poznańskie Studia Teologiczne, 2010)
The main point is presentation of J. Hick’s conception of religious faith freedom and her critics. On this ground article put questions to catholic’s theology. Hick say that faith is experiencing-as, and has almost infinite freedom. God can't to force to believe Him. From the other side. Hick consider that person like Jesus had huge awareness of God’s, that it was no place for freedom. Authors like Perret, Henze, Cheetham try to analyze Hik’s conception. They shows few contradictions and new problems.